Administration of Vitamin D Metabolites Affects RNA Expression of Xenobiotic Metabolising Enzymes and Function of ABC Transporters in Rats - Klumpp, Karoline (2019)
From studies on different species and in cell culture systems, it has been suggested that vitamin D metabolites might affect themetabolism and elimination of xenobiotics. Although most studies performed on rodents and cell cultures report an upregulationof respective enzymes and transporters, data from the literature are inconsistent. Especially results obtained with sheep differ fromthese observations. As vitamin D metabolites are widely used as feed additives or therapeutics in livestock animals, we aimed toassess whether these differences indicate species-specific responses or occurred due to the very high dosages used in the rodentstudies. -erefore, we applied treatment protocols to rats that had been used previously in sheep or cattle. Forty-eight female ratswere divided into three treatment and corresponding placebo groups: (1) a single intraperitoneal injection of 1,25-(OH)2D3 orplacebo 12 h before sacrifice; (2) daily supplementation with 25-OHD3 by oral gavage or placebo for 10 days; and (3) a singleintramuscular injection of vitamin D3 10 days before sacrifice. In contrast to a previous study using sheep, treatment of rats with1,25-dihydroxyvitamin D3 did not result in an upregulation of cytochrome P450 3A isoenzymes (CYP3A), but a decrease wasfound in hepatic and intestinal expressions. In addition, a downregulation of P-glycoprotein (P-gp) and breast cancer resistanceprotein was found in the brain. Taken together, the stimulating effects of vitamin D metabolites on the expression of genesinvolved in the metabolism and elimination of xenobiotics reported previously for rodents and sheep could not be reproduced. Incontrast, we even observed a negative impact on the expression of CYP3A enzymes and their most important regulator, thepregnane X receptor. Most interestingly, we could demonstrate an effect of treatment with 25-hydroxyvitamin D3 and vitamin D3on the functional activity of ileal P-glycoprotein (P-gp) using the Ussing chamber technique.